Potential Mechanisms of Lactate Dehydrogenase and Bovine Serum Albumin Proteins as Antioxidants: A Mixed Experimental–Computational Study - Jing Ye; Amy Bounds; Madeline Crumpton; Mallory Long; Haley McDonough; Isabella Srikhirisawan; Shanzhen Gao (Biochemistry Research International)
Proteins have shown varying degrees of antioxidant activity. This study examined the potential mechanisms of interactions between proteins and radicals using chemical kinetics and computational methods. The study quantified the antioxidant activity of lactate dehydrogenase (LDH) and bovine serum albumin (BSA) through Trolox equivalent antioxidant capacity (TEAC) and oxygen radical absorbance capacity (ORAC) assays. BSA was about seven times and LDH 12 times more potent as antioxidants for 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate) (ABTS•−) than they were for peroxyl radicals. According to the evaluation of Trolox equivalents (TE) of 20 proteinogenic amino acids, tryptophan (with a TE value of 101 μmol TE/μmol) exhibited the highest antioxidant activity for ABTS•−, followed by tyrosine (38.7 μmol TE/μmol) and cysteine (30.5 μmol TE/μmol), lysine (0.193 μmol TE/μmol), arginine (0.0325 μmol TE/μmol), valine (0.0280 μmol TE/μmol), histidine (0.00689 μmol TE/μmol), and leucine (0.00560 μmol TE/μmol). The EC50 showed a similar order with a swap between valine and histidine. The antioxidant activity of the amino acids and proteins was temperature dependent. The rate laws, activation energy, and pre-exponential factor A of these reactions provided information on the reaction mechanisms, i.e., a biomolecular elementary step for the reaction of ABTS•− with amino acids tryptophan, tyrosine, cysteine, or protein LDH, and a more complicated mechanism for BSA. The presence of –NH– or hydroxyl groups on aromatic rings enhanced the antioxidant ability of tryptophan and tyrosine. LDH’s antioxidant activity did not affect its enzymatic activity, indicating that the radical reaction likely happened on the protein’s surface without significantly altering its conformation. The molecular modeling and visualization showed potential reaction sites on the proteins’ accessible tryptophan and tyrosine residues. However, the mere surface exposure of tryptophan and tyrosine does not guarantee their antioxidant activities.